2019
DOI: 10.1155/2019/7132843
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Fracture Propagation Induced by Supercritical CO2 in Inter-Salt-Shale Reservoir

Abstract: Hydraulic fracturing using freshwater is difficult for the commercial exploitation of a shale oil reservoir in Jianghan Basin with a continental saline lake basin sedimentary background. Supercritical CO2 (SC-CO2) is a promising fracturing fluid under consideration for the reservoir stimulation, especially in the case of the presence of water sensible salt layers. In this study, SC-CO2 fracturing experiments on the inter-salt-shale and salt specimens, which were obtained from the drilling well, were carried ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Wang [100] and other studies have found that natural fractures with high cementation strength almost do not affect the fracture propagation path, while natural fractures with low cementation strength or an original opening have a greater impact on fracture propagation. Zhang et al [101] showed that the fracture pressure of salt rock is higher than that of inter-salt shale. Deng et al [102] carried out fracturing simulation experiments and found that under high-level stress differences, the opening of the original weak surface may lead to shear failure.…”
Section: Crack Growth Law Of Supercritical Co 2 Fracturingmentioning
confidence: 99%
“…Wang [100] and other studies have found that natural fractures with high cementation strength almost do not affect the fracture propagation path, while natural fractures with low cementation strength or an original opening have a greater impact on fracture propagation. Zhang et al [101] showed that the fracture pressure of salt rock is higher than that of inter-salt shale. Deng et al [102] carried out fracturing simulation experiments and found that under high-level stress differences, the opening of the original weak surface may lead to shear failure.…”
Section: Crack Growth Law Of Supercritical Co 2 Fracturingmentioning
confidence: 99%